An Implementation of Remote Monitoring Standing Tree Diameter at Breast Height - Liyuan Jiang; Wenbin Li; Jiangming Kan; Zhibin Hao; Qing Xu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Studies show that there is electric potential difference between the internal part of tree and the soil, but the mechanism is not clear, possibly associated with tree species, environmental factors and DBH (diameter at breast height) of tree. In order to research the mechanism and change rules, it is necessary to measure bioelectricity, environmental factors and DBH of tree, among which the DBH and its growth is an important indicator. A kind of DBH of tree and its growth automatic measuring system has been designed based on the angular displacement sensor. The system can realize remote monitoring function of DBH measurement and the growth, and can be set by structural parameters to measure the size of DBH. In this paper, the experiments require the DBH of tree ranges from 0~40cm, and calculation system can measure the DBH less than 0.0436mm theoretically, meeting the measurement requirements and providing reliable data for researching mechanism of trees. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3489